2019
DOI: 10.1093/mnras/stz2379
|View full text |Cite
|
Sign up to set email alerts
|

GMRT observations of a first sample of ‘Extremely Inverted Spectrum Extragalactic Radio Sources (EISERS)’ candidates in the Northern sky

Abstract: We present an extension of our search for 'Extremely Inverted Spectrum Extragalactic Radio Sources' (EISERS) to the northern celestial hemisphere. With an inverted radio spectrum of slope α > +2.5, these rare sources would either require a non-standard particle acceleration mechanism (in the framework of synchrotron self-absorption hypothesis), or a severe free-free absorption which attenuates practically all of their synchrotron radiation at metre wavelengths. By applying a sequence of selection filters, a li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Our sources have optically thick spectral index constraints that are consistent with SSA, though improved spectral coverage at low frequencies (<1 GHz) will ultimately be needed (Callingham et al 2015;Collier et al 2018;Keim et al 2019;Mhaskey et al 2019aMhaskey et al , 2019b. The identification of FFA associated with any of the newly radio-loud AGNs in our sample would be of particular interest in the context of galaxy evolution since simulations have shown that it may arise from jet−ISM interactions (Bicknell et al 1997(Bicknell et al , 2018.…”
Section: Radio Color-color Diagrammentioning
confidence: 65%
See 1 more Smart Citation
“…Our sources have optically thick spectral index constraints that are consistent with SSA, though improved spectral coverage at low frequencies (<1 GHz) will ultimately be needed (Callingham et al 2015;Collier et al 2018;Keim et al 2019;Mhaskey et al 2019aMhaskey et al , 2019b. The identification of FFA associated with any of the newly radio-loud AGNs in our sample would be of particular interest in the context of galaxy evolution since simulations have shown that it may arise from jet−ISM interactions (Bicknell et al 1997(Bicknell et al , 2018.…”
Section: Radio Color-color Diagrammentioning
confidence: 65%
“…In a future study, we will incorporate new data from forthcoming VLA and Giant Metre-wave Radio Telescope (GMRT) observations spanning a broader frequency range (the full contiguous frequency range of the VLA from 1 to 50 GHz and deep measurements below 1 GHz using the VLA and GMRT). This will enable a more rigorous radio SED modeling analysis that will allow us to test whether SSA or FFA is responsible for the observed spectral curvature (Mhaskey et al 2019a(Mhaskey et al , 2019b.…”
Section: Radio Sed Modelingmentioning
confidence: 99%
“…FFA has been suggested to occur in a disk (Marr et al, 2001), a torus (Peck et al, 1999;Kameno et al, 2000Kameno et al, , 2001Kameno et al, , 2003, and in ambient clouds shocked by the expanding radio source, producing a power-law distribution of electron density in the ionized ambient clouds (Bicknell et al, 1997(Bicknell et al, , 2018. There is supporting evidence from individual sources whose spectra are better fit by FFA rather than by SSA (e.g., Bicknell et al, 1997;Peck et al, 1999;Kameno et al, 2000Kameno et al, , 2001Kameno et al, , 2003Marr et al, 2001Marr et al, , 2014Callingham et al, 2015;Mhaskey et al, 2019a) and see Krishna et al (2014), Callingham et al (2017) and Mhaskey et al (2019b) for additional candidates. The FFA is generally consistent with an ionized medium with a temperature T∼ 10 4 K, path length ∼ 1 − 100 pc, and an electron density n e ∼ 10 3 − 10 4 cm −3 .…”
Section: What Causes the Turnover In The Radio Spectrum?mentioning
confidence: 98%
“…There are some PS sources for which free‐free absorption (FFA) is a better fit to the radio spectrum turnover than synchrotron self‐absorption (Bicknell et al 1997; Callingham et al 2015; Kameno et al 2000, 2001, 2003; Marr et al 2001, 2014; Mhaskey et al 2019; Peck et al 1999; Tingay et al 2015). The required dense clouds of ionized thermal electrons may be produced by shock ionization of dense gas clouds by the expanding radio source (Bicknell et al 1997) or by clouds engulfed by the cocoon (Begelman 1999).…”
Section: Opportunitiesmentioning
confidence: 99%